Endoplasmic reticulum stress and diabetic retinopathy - Toshiyuki Oshitari; Natsuyo Hata; Shuichi Yamamoto (Vascular Health and Risk Management, 2008)
Toshiyuki Oshitari1,2, Natsuyo Hata1, Shuichi Yamamoto11Department of Ophthalmology and Visual Science, Chiba University Graduate School of Medicine, Chiba City, Chiba, Japan; 2Department of Ophthalmology, Kimitsu Central Hospital, Kisarazu City, Chiba, JapanAbstract: Endoplasmic reticulum (ER) stress is involved in the pathogenesis of several diseases including Alzheimer disease and Parkinson disease. Many recent studies have shown that ER stress is related to the pathogenesis of diabetes mellitus, and with the death of pancreatic β-cells, insulin resistance, and the death of the vascular cells in the retina. Diabetic retinopathy is a major complication of diabetes and results in death of both neural and vascular cells. Because the death of the neurons directly affects visual function, the precise mechanism causing the death of neurons in early diabetic retinopathy must be determined. The ideal therapy for preventing the onset and the progression of diabetic retinopathy would be to treat the factors involved with both the vascular and neuronal abnormalities in diabetic retinopathy. In this review, we present evidence that ER stress is involved in the death of both retinal neurons and vascular cells in diabetic eyes, and thus reducing or blocking ER stress may be a potential therapy for preventing the onset and the progression of diabetic retinopathy.Keywords: endoplasmic reticulum stress, diabetic retinopathy, vascular cell death, neuronal cell death